The Impact of a Metacognitive Intervention on Student Experiences and Success in an Academic Probation Program for First-Year Students - Swanson, Holly J.; Dewsbury, Bryan (Teaching and Learning Inquiry, 2024)
First-year students often struggle with self-regulated learning, particularly in monitoring and accurately assessing their level of understanding and translating that into appropriate preparation for rigorous post-secondary coursework. When their academic struggles become extreme, they can be placed in probationary programs. An intervention involving weekly reflective surveys focused on study strategies and metacognitive skill development was integrated into one such probationary program for first-year students. During the intervention, a slightly higher rate of successful completion of the program was observed compared to previous years. The self-reported experiences and patterns of engagement of the students suggested that the intervention positively impacted metacognitive skill development and additionally provided evidence of the importance of motivation at various points throughout the process. Identifying appropriate timepoints for intervention can better prepare stakeholders to support those students who may not be retained. Read the corresponding ISSOTL blog post here.